Musculoskeletal Disorders and Quality of Life in Chilean Teachers: A Cross-Sectional Study - Vega-Fernández, Gustavo; Olave, Enrique; Lizana, Pablo A. (Frontiers in Public Health, 2022)
Introduction Teaching professionals have reported multiple conditions associated with low quality of life (QoL) perception. Various studies have also reported high prevalence of musculoskeletal disorders (MSD). In this context, there are few studies regarding the association between low QoL perception and MSD suffering in teachers. Objective Therefore, in this study the aim was evaluate MSD prevalence and its association with teachers' QoL perception. Participants and Methods A total sample of 544 Chilean teachers were included in a cross-sectional study. MSD prevalence was evaluated via the Standardized Nordic Questionnaire and QoL perception via the Short-Form 36 Health Survey Instrument. Multinomial logistic regression was applied to evaluate the association between MSD and QoL perception adjusted for gender and age. Results A total of 91% of teachers have had some MSD in the last 12 months, and 28.86% have had 6 or more painful regions. Females showed greater MSD prevalence than males. Teachers who reported no MSD had higher QoL scores compared to teachers with MSD. The group of teachers with the most MSD (≥p75) saw significant increases in the risk of having low scores in the physical (OR: 2.82) and mental components (OR: 2.65) of QoL. By contrast, teachers without MSD have a buffer effect for their QoL (physical OR: 0.2; mental OR: 0.44). Conclusions High MSD prevalence suggest that preventive and informative actions must be taken regarding these disorders to protect teachers' mental and physical health, considering the multiple risk factors to which teachers are exposed given their work conditions in Chile and worldwide.